CRIMINAL LAW POLICY IN IMPLEMENTATION LEGAL PROCESS AGAINST GENERAL CRIME WHAT IS DONE BY INDONESIAN NATIONAL ARMY SOLDIERS - Handoko Handoko (Jurnal Hukum Khaira Ummah, 2022)
This thesis examines the policy of criminal law in the implementation of the legal process against general crimes committed by Indonesian National Armed Forces Soldiers. Starting from Law Number 34 of 2004 concerning the Indonesian National Army, Article 65 Paragraph 2 which regulates soldiers to be subject to the power of the military courts in the case of violations of the military criminal law and subject to the powers of the general courts in the case of violations of the general criminal law. This brings a very basic change, because so far the military court has the authority to process the law to try all crimes committed by soldiers, both military crimes and general crimes. This type of research is normative legal research with a normative juridical approach.Keywords : Criminal law policy, Legal process, Soldiers who commit general crimes.